Cover Feature: Stopped‐Flow 19F NMR Spectroscopic Analysis of a Protodeboronation Proceeding at the Sub‐Second Time‐Scale (Eur. J. Org. Chem. 17/2021). Issue 17 (20th April 2021) - Wei, Ran; Hall, Andrew M. R.; Behrens, Richard; Pritchard, Mark S.; King, Edward J.; Lloyd‐Jones, Guy C.
Abstract : The Cover Feature shows a young researcher looking into the vast starry sky, accompanied by an NMR spectrometer. The shooting stars represent the fleeting information embedded in rapid irreversible chemical reactions, for example, the base‐catalyzed protodeboronation of penta‐fluorophenyl boronic acid which has a half‐life of 0.12 s. With the aid of a stopped‐flow NMR technique, the researcher is able to capture the information from the rapidly evolving reactions, to gain information that will shed light on the reaction mechanism. More information can be found in the Full Paper by G. C. Lloyd‐Jones et al.